Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Suku Dinas Perhubungan Jakarta Selatan - Muhammad Husni Irhamsyah husni; A. Fauzan Fadlan fauzan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to determine the effect of motivation and work environment on the performance of employees of the South Jakarta Transportation Department. This study uses a quantitative approach and uses primary data through distributing questionnaires to 83 respondents to employees of the South Jakarta Transportation Agency. The sampling technique used simple random sampling. Data were processed through the SPSS version 25.0 program with multiple linear regression analysis techniques. The results of the t test prove that partially motivation has a significant effect on employee performance with a significance value of 0.000 <0.05, while the work environment has a significant effect on employee performance as shown by the acquisition of a significant value of 0.000 <0.05. Then the results of the F test prove that motivation and work environment simultaneously have a significant effect on the performance of the employees of the South Jakarta Transportation Agency with a significance value of 0.000 <0.05. The contribution of the influence of motivation (X1) and work environment (X2) on employee performance (Y) was 73.7%, while the remaining 26.3% contained other factors which were not examined in this study.